Скорость полета, частота взмахов крыльями и энергетика полета чайки морской голубок - Цвелых, А.Н. (Вестник зоологии, 1988)
A direct correlation is revealed between the flight speed, wingbeat frequency in Gulls and some other bird species. The Gulls flying to the breeding colony increase flight speed as related to flight weight increase due to increased in Lestina 1 content.